Evolution mechanism of interfacial microstructure and regulation of mechanical properties of laser-arc hybrid weld-brazing aluminum/steel joints under different post-welding heat-treatment temperatures - Yunqi Liu; Fei Li; Yuanxing Li; Zongtao Zhu; Hui Chen (Journal of Materials Research and Technology, 2024)
Control of the interfacial microstructures and mechanical properties of aluminum/steel joints after welding is crucial to prolonging the service lives of such structures. In this study, the influence of post-welding heat treatment (PWHT) on aluminum/steel laser-arc weld-brazing joints was investigated, with particular focus on the evolution mechanisms of the interfacial microstructures and regulation of the mechanical properties. Transmission electron microscopy (TEM) and electron backscatter diffraction (EBSD) results confirmed the presence of the monoclinic Fe4Al13 and hexagonal Al8Fe2Si phases at the aluminum/steel interface. Upon increasing the heat-treatment temperature, micro-characteristics of the intermetallic compound (IMC) passed through three different stages (weak elemental diffusion–reaction–drastic change) depending on the temperature employed; these stages differed from the PWHT phenomenon observed for the aluminum/steel solid-state welded joints. EBSD analyses revealed decreases in the grain size and textural strength of the IMC layer following PWHT at 180 °C/1 h, while the Fe4Al13 phase gradually transformed into Al8Fe2Si phase during PWHT at 520 °C/1 h, ultimately leading to an increase in the grain size and a higher textural strength. Additionally, PWHT effectively eliminated the residual tensile stress in aluminum/steel joints and improved the softening of the heat-affected zone (HAZ). Upon PWHT at 180 °C/1 h, the synergistic effects of the elimination of residual stress, an enhanced softening in the HAZ, and changes in the IMC layer, led to improved joint properties. Furthermore, the maximum tensile strengths of the joints with and without reinforcement increased to 221.9 MPa (from 209.8 MPa) and 165.3 MPa (from 148.1 MPa), respectively.